Carceral Geography: a propósito del giro espacial y las ciencias sociales - Bosio, Gaston (Universidad Nacional del Litoral, 2020)
This article reflects on the book published in 2015 by Dominique Moran, whose purpose is to lay the foundations for a new sub-discipline within Human Geography. This is Carceral Geography. Spaces and Practices of incarceration, where the main points of view of carceral geography are presented, describing several authors from whom it has been nourished and suggesting future fields and lines of research that enhance this new area of study. This text also reviews those works of Moran that somehow preceded and announced the intention of founding carceral geography, to finally adopt a critical perspective on the Moran’s chosen path. Due the importance of the notion of space for carceral geography, we present a brief series of debates on this issue.